Layanan Mobile Digital Islamic Network dan Kepuasan Nasabah PT Bank Muamalat - Sapiri, Muhtar; Awaluddin, Murtiadi; Sijal, Mutakallim; Nur, Fira (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Changes in people's behavior and needs in utilizing digital technology to carry out banking activities independently are taking place very rapidly. This is proven by the number of e-banking users (SMS banking, telephone banking, mobile banking and internet banking which increased by 270% in the 2012 – 2016 period. Moreover, with the digital acceleration in recent years after Covid-19, the number of e-banking users has drastically increased, especially digital transactions via mobile banking with 24.21 million users in 2020. This research was conducted to evaluate the features of the Muamalat Digital Islamic Network (DIN) mobile banking service. In this case, researchers will focus on evaluating speed, security, accuracy and trust in the Muamalat DIN mobile banking application and its relationship with customer satisfaction. The research method used is to use the Importance Performance Analysis (IPA) method or analysis of the level of importance and performance through GAP analysis and quadrant analysis. The data was obtained by distributing questionnaires to customers using the Muamalat DIN Makassar Branch Office mobile banking. The sampling technique is carried out using the Hair formula, where if the population size is unknown then use a size of 5-10 multiplied by the research instrument variable. The research results show that there are 6 attributes in quadrant II in the